Achieving Sustainable Inter‐City Transport in Ireland - CAULFIELD, BRIAN (My University, 2011)
Over the past decade the Irish government has invested intensively in a large national motorway network. One of the side effects of this investment has been that now inter-city travel is now considerably cheaper and quicker by car over any other mode. The main objective of this research is to identify and examine the barriers to sustainable inter-city transport in Ireland. The majority of sustainable transport research takes place in an urban context with very little research has focused on understanding the factors to encourage alternative modes on inter - city trips. A stated preference study was conducted to determine what are the factors that impact upon individuals‟ mode choice when conducting an inter-city trip. The results of this paper demonstrate that there are several factors that impact upon individuals‟ mode choice decisions when undertaking an inter-city trip. The main factor that was found to impact upon mode choice was the requirement to have a car in the destination city.
ITRN 2011
PUBLISHED
UCC
Keywords: Transport; Smart & Sustainable Planet